Taking chances: the effect of growing up on welfare on the risky behavior of young people - Deborah A. Cobb-Clark; Chris Ryan; Anastasia Sartbayeva (Institute for the Study of Labor (IZA), 2009)
We analyze the effect of growing up on welfare on young people's involvement in a variety of social and health risks. Young people in welfare families are much more likely to take both social and health risks. Much of the apparent link between family welfare history and risk taking disappears, however, once we account for family structure and mothers' decisions regarding their own risk taking and investment in their children. Interestingly, we find no significant effect of socio-economic status per se. Overall, we find no evidence that growing up on welfare causes young people to engage in risky behavior.
urn:nbn:de:101:1-2009040384
Keywords: J13; I38; J18; 330; Youths; welfare; risky behavior; socio-economic disadvantage; Jugendliche; Jugendsoziologie; Sozialhilfeempfänger; Soziales Verhalten; Gesundheitsrisiko; Australien